Pre-service science teachers’ understanding of the concepts relating to diffusion, osmosis, and the particulate nature of matter and their attitudes towards science - Alharbi, Nawaf Nahiss Alsheatr (Curtin University, 2012)
This study investigated understanding of diffusion, osmosis and particle theory of matter concepts among pre-service science teachers in Saudi Arabia using a 17-item two-tier multiple choice diagnostic test that was adapted from two previously developed instruments in the research literature. The participants were 192 preservice science teachers from 15 Saudi Arabian teachers' colleges who were in the second and third years of a 4-year course leading to a bachelor degree. In addition, the study evaluated the pre-service science teachers’ attitudes to science using 30 items from the Test of Science-Related Attitudes (TOSRA) questionnaire. Analyses of their responses indicated that the total score for the eight diffusion and osmosis items ranged from 3 to 8, while the total score for the nine particle theory items ranged from 3 to 7. The correct responses to the osmosis and diffusion items and those to the particle theory items were significantly correlated (Pearson correlation = 0.42, p < 0.01).On the whole, correct responses to both tiers of the items of the diagnostic test were lower than those for the first tier only. For example, for the eight items on osmosis and diffusion, 60.4% to 93.4% of pre-service teachers provided correct responses to the first tier, whereas only 44.9% to 70.5% provided correct responses to both tiers. As for the nine items on the particle theory, 51.5% to 88.6% provided correct responses to the first tier, whereas only 41.0% to 63.0% provided correct responses to both tiers of the items. Pre-service teachers’ attitudes to science were evaluated using three dimensions of the TOSRA, namely, Adoption of Scientific Attitudes, Enjoyment of Science Lessons, and Attitude to Scientific Inquiry. The mean scores of these three dimensions of the TOSRA were highly correlated to each other, the Pearson correlations ranging from 0.44 to 0.49 with p < 0.01 in each case.Several alternative conceptions—that were held by more than 10% of the preservice teachers—were identified in this study. For osmosis and diffusion, these alternative conceptions included misconceptions about the difference between the two concepts, the process of osmosis itself, understanding of a semi-permeable membrane, and the effect of temperature on solubility. In the case of the particle theory, the alternative conceptions that were identified were related to understanding of changes of state, the process of dissolution, confusion between macroscopic and submicroscopic properties of substances, particle arrangement in the three states of matter, and diffusion in gases and liquids. Interviews with the pre-service teachers provided useful insights into their understanding of the concepts that were evaluated by the diagnostic test as well as about their confidence in teaching these concepts on completing their studies.The author recognised that there is need for developing a curriculum that will help pre-service teachers in understanding the basic concepts related to diffusion, osmosis and the particulate nature of matter. At the same time, classroom instruction in teachers’ colleges in Saudi Arabia should be more relevant to student teachers’ everyday experience in order that they may adopt more positive attitudes towards science.